2017
DOI: 10.12681/jhvms.14852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening for Blastocystìs sp. in canine faecal samples in Greece

Abstract: • Μοριακή αναζήτηση της Blastocystìs sp. σε κόπρανα σκύλου στην Ελλάδα. ABSTRACT.Blastocystìs is an anaerobic parasitic microorganism which has been found in the intestinal tract of many vertebrates including humans and dogs. Recently, members of Blastocystìs sp. were classified into nine sub-types, based on phylogenetic trees derived from sequence analysis of the small sub-unit ribosomal RNA gene. The pathogenesis of Blastocystìs in the dog remains uncertain and the existence of pathogenic and non-pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The occurrence of the parasite was reported to be about only 3.0% using direct -light microscopy in a population of 130 domestic dogs from the Sharkia and Qalyubia governorates, also located in northern Egypt [35]. Using molecular methods, the parasite was not identified in dogs in numerous countries, including Spain [58], Poland [59] and Greece [60], but was found with low occurrence in France (3.4%) [61], Australia (2.5%) and Cambodia (1.3%) [62]. In a survey conducted in Southern China [63], the authors showed significant differences in the prevalence of Blastocystis sp.…”
Section: Resultsmentioning
confidence: 98%
“…The occurrence of the parasite was reported to be about only 3.0% using direct -light microscopy in a population of 130 domestic dogs from the Sharkia and Qalyubia governorates, also located in northern Egypt [35]. Using molecular methods, the parasite was not identified in dogs in numerous countries, including Spain [58], Poland [59] and Greece [60], but was found with low occurrence in France (3.4%) [61], Australia (2.5%) and Cambodia (1.3%) [62]. In a survey conducted in Southern China [63], the authors showed significant differences in the prevalence of Blastocystis sp.…”
Section: Resultsmentioning
confidence: 98%